2014
DOI: 10.1001/jamaoto.2014.1671
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes in Advanced Laryngeal Cancer

Abstract: Surgical therapy leads to better survival outcomes than nonsurgical therapy for patients with advanced laryngeal cancer. Patients need to be made aware of the modest but significant survival disadvantage associated with nonsurgical therapy as part of the shared decision-making process during treatment selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
237
4
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(269 citation statements)
references
References 8 publications
15
237
4
13
Order By: Relevance
“…The outcomes of treatment of the subset of patients with T3 laryngeal cancer with N0 disease reported by Megwalu and Sikora, 7 showed inferior 5-year OS (48% vs 59%) and DSS (63% vs 69%) for larynx preservation compared to the surgical cohort. However, the discrimination between IMRT and conventional RT is not possible, and dichotomizing RT alone and CRT for larynx preservation cannot be performed in this Surveillance, Epidemiology, and End Results database.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The outcomes of treatment of the subset of patients with T3 laryngeal cancer with N0 disease reported by Megwalu and Sikora, 7 showed inferior 5-year OS (48% vs 59%) and DSS (63% vs 69%) for larynx preservation compared to the surgical cohort. However, the discrimination between IMRT and conventional RT is not possible, and dichotomizing RT alone and CRT for larynx preservation cannot be performed in this Surveillance, Epidemiology, and End Results database.…”
Section: Discussionmentioning
confidence: 93%
“…[3][4][5][6][7] For example, Hoffman et al, 3 using a robust NCDB, reported that increased use of nonsurgical approaches for larynx preservation was concurrent with decreased relative survival in patients with T3 laryngeal cancers. However, because Hoffman et al 3 culled data from between 1985 and 2001, before the implementation of IMRT and the publication of RTOG 9001 and the more widespread use of induction and concurrent chemotherapy, their findings, although timely when published, do not accurately reflect the use of RT and combined modality techniques in the current era.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations